Treatment of fracturing wastewater by anaerobic granular sludge: The short-term effect of salinity and its mechanism. (February 2022) - Zhang, Anlong; Gao, Chuyue; Chen, Tiantian; Xie, Yili; Wang, Xianbao
Graphical abstract: Highlights: Anaerobic digestion of fracturing wastewater was impacted when salinity exceed 15 g/L. High salinity decreased granular size and the activity of granular sludge. Percentage of damaged cell in granular sludge increased with increase of salinity. High salinity reduced the diversity and the abundance of methanogens. Abstract: The effects of salinity shock on the anaerobic treatment of fracturing wastewater regarding chemical oxygen demand (COD) removal performance, sludge characteristics and microbial community were investigated. Results showed COD removal efficiency decreased from 76.0% to 69.1%, 65.6%, 33.7% and 21.9% with the increase of salinity from 2.5 g/L to 10, 15, 25 and 45 g/L, respectively. The cumulative biogas production decreased by 13.8%–81.1% when salinity increased to 15–85 g/L. The increase of salinity led to the decline in particle size of granular sludge, and the activity of granular sludge, including SMA, coenzyme F420 and dehydrogenase, was inhibited significantly. Flow cytometry indicated the percentage of damaged cells in granular sludge gradually increased with the increase of salinity. Sequence analysis illustrated that microbial community structure in anaerobic digestion reactor was influenced by the salinity, high salinity reduced the diversity of archaea and decreased the abundance of methanogens, especially Methanosaeta.